Manipulation of probiotics fermentation of yogurt by cinnamon and licorice: effects on yogurt formation and inhibition of helicobacter pylori growth in vitro - Behrad, S.; Yusof, M.Y.; Goh, K.L.; Baba, A.S. (2009)
Probiotic bacteria especially Lactobacillus spp. And Bifidobacterium exert suppressive effect on Helicobacter pylori. Cinnamon and licorice have been traditionally used for the treatment of gastric ulcer. The objectives of this study were to determine the effects of herbs on yogurt fermentation, the level of probiotic bacteria in yogurt during 28 days storage and the effect of herbal yogurt on the growth of H. pylori in vitro. Cinnamon or licorice was mixed with milk and the mixture was fermented with probiotic bacteria to form herbal-yogurt. Changes of pH and total titratable acids were monitored and the viability of probiotic bacteria was evaluated during and after refrigerated storage. The in vitro inhibition of H. pylori growth was determined using agar diffusion and minimum inhibitory concentration (MIC) method. The presence of herbs did not affect the probiotic population during storage. There were no significant differences in pH and TTA between herbal-yogurts and plain-yogurt during fermentation and storage. Water extract of cinnamon-yogurt showed the highest inhibition effect (13.5mm) on H. pylori growth in comparison with licorice-yogurt (11.2mm). The present findings indicate cinnamon and licorice has bioactive components to decrease the growth of H. pylori.